Pyoderma Gangrenosum in Two Successive Pregnancies Complicating Caesarean Wound - Sapna Vinit Amin; Neha Bajapai; Ashwini Pai; Sunanda Bharatnur; Shripad Hebbar (Hindawi Limited, 2014)
Pyoderma gangrenosum (PG) is a rare ulcerative cutaneous disorder with tendency to recur in the injured area. Though most of the time is associated with chronic systemic conditions, it can occur in isolation and can be a diagnostic dilemma. The aetiology is poorly understood. The diagnosis is based on clinical features and excluding other causes of skin ulcers, as it does not have characteristic histopathology or laboratory findings. Lesions can develop after surgery, after trauma or de novo. We are reporting a 32-year-old pregnant lady with two previous instances of pyoderma gangrenosum in the previous pregnancy, who in postoperative period following caesarean section developed the same condition for the third time. She responded well to local wound care, oral Prednisolone, and Dapsone and made a good recovery. Pregnancy being an immunologically altered status can play a role in development of pyoderma gangrenosum and one should always rule out its possibility when there is a delayed wound healing.